2019
DOI: 10.1021/acs.inorgchem.9b00807
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Vanadium(IV) Species with Ubiquitin: A Combined Instrumental and Computational Approach

Abstract: The interaction of VIVO2+ ion and five VIVOL2 compounds with potential pharmacological application, where L indicates maltolate (ma), kojate (koj), acetylacetonate (acac), 1,2-dimethyl-3-hydroxy-4­(1H)-pyridinonate (dhp), and l-mimosinate (mim), with ubiquitin (Ub) was studied by EPR, ESI-MS, and computational (docking and DFT) methods. The free metal ion VIVO2+ interacts with Glu, Asp, His, Thr, and Leu residues, but the most stable sites (named 1 and 2) involve the coordination of (Glu16, Glu18) and (Glu24, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 116 publications
1
23
0
Order By: Relevance
“…to those revealed with V III and recently published, that indicate the formation of the adducts n[V IV O(acac)]-Ub, with n = 1-3 (Ugone et al, 2019). For the system containing Ub as well, EPR measurements indicated the complete transformation of V III (acac) 3 to V IV O(acac) + moiety, which in solution interacts with ubiquitin ( Figure 3B).…”
Section: Interaction Of V Iii (Acac) 3 and V Iv O(acac) 2 With Proteinssupporting
confidence: 77%
See 2 more Smart Citations
“…to those revealed with V III and recently published, that indicate the formation of the adducts n[V IV O(acac)]-Ub, with n = 1-3 (Ugone et al, 2019). For the system containing Ub as well, EPR measurements indicated the complete transformation of V III (acac) 3 to V IV O(acac) + moiety, which in solution interacts with ubiquitin ( Figure 3B).…”
Section: Interaction Of V Iii (Acac) 3 and V Iv O(acac) 2 With Proteinssupporting
confidence: 77%
“…The two solutions are displayed in Figures 5A,B, showing that with increasing the strength of the axial interaction with Ala107 decreases the strength of the contact of V=O with Trp63 and viceversa; in When the interaction of V IV O species and ubiquitin is examined, the data indicated that two main sites exist. The first is based on the coordination of (Glu 16, Glu18; site 1) or (Glu18, Asp21; site 1') (Ugone et al, 2019); the two sites are mutually exclusive and have F mean in the range 39.3-44.3 with population between 14 and 20%. The second site is due to the equatorial binding of the couple (Glu24, Asp52; site 2) or (Glu51, Asp52; site 2') (Ugone et al, 2019); in this case too, these sites are not independent with F mean = 34.9-37.2 and population = 12-88%.…”
Section: Interaction Of V Iii (Acac) 3 and V Iv O(acac) 2 With Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…7). The described integrated strategy has been used in a series of works to fully rationalize and characterize the binding sites of V IV O 2+ to other abundant serum proteins, namely, Hb, apo-hTf 143 and holo-hTf, and IgG, as well as to model proteins, such as ubiquitin (Ub) 144 and myoglobin (Mb). 145 We believe that, since V IV O 2+ is the most important active species released by antidiabetic and antitumor VCs, characterization at the molecular level of its binding sites could open new possibilities to understand the mechanism of action of novel V based drugs.…”
Section: IV O 2+ Bindingmentioning
confidence: 99%
“…Oxovanadium complexes chelated by two acetylacetonate ligands form a five-coordinate bonding system that can act as a Lewis acid (Nenashev et al 2015;Ugone et al, 2019;Costa Pessoa, 2015;Correia et al 2017). This system can undergo a reaction with a Lewis base to increase its coordination ISSN 2056-9890 bonding number to six.…”
Section: Chemical Contextmentioning
confidence: 99%